Effect of PGF 2a on parturition induction, litter performance and oestrus synchronization in brood sows - KYRIAKIS, S.; STOITSIOU, C.; TSALTAS, C.; TSAKALOF, P. (Journal of the Hellenic Veterinary Medical Society, 2019)
The experiment was conducted in a livestock unit of 500 brood sows and comprised a total of 40 animals, of the same genetic potential and reared under the same management conditions. Of these animals, 20 were injected with 12mg PGF2a (group T2) between days 109-113 of pregnancy, while the remaining 20 (group Tl) were used as controls. All parturitions were unevenful and were induced 36.7 ± 2.63 hrs after the injection of PGF2a· The results of the administration of PGF2a to the animals of group T2, in comparison with those of group Tl, can be summarised as follows: 1) Duration of pregnancy: Tl= 113.9 ± 0.65 days, T2= 111.2 ± 0.64 days (P/0.001). 2) No difference was observed in the number of piglets born and the survival rate of the litters, 1,21, 30 and 45 days after farrowing. 3) The mean body weights showed significant differences on parturition (P/0.005), and on the 21st (P/0.001), the 30th (P/0.001 day of weaning) and the 45th day of life (P/0.01 - difference of 1,103 kg) in favour of the controls (group Tl). 4) The animals of group Tl showed oestrus and were bred 7.9 ± 1.77 days after weaning (80% of the sows in oestrus - conception rate 90%), while these of group T2 showed oestrus and were bred 5,55 ± 0.63 days after weaning (85% of the sows in oestrus – conception rate 85%) (P/0.02). 5) At the subsequent parturition that occurred without any treatment, no difference whatsoever was observed in any animal of both experimental groups